2006
DOI: 10.1016/j.ymthe.2005.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Vascular bed-targeted in vivo gene delivery using tropism-modified adeno-associated viruses

Abstract: Virus-mediated gene delivery is restricted by the infectivity profile of the chosen vector. Targeting the vascular endothelium via systemic delivery has been attempted using peptides isolated in vitro (using either phage or vector display) and implicit reliance on target receptor expression in vivo. This has limited application since endothelial cells in vitro and in vivo differ vastly in receptor profiles and because of the existence of complex endothelial "zip codes" in vivo. We therefore tested whether in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 37 publications
2
101
1
1
Order By: Relevance
“…Targeted delivery of endothelial nitric oxide synthase (eNOS) transgene to ECs prevented elevation of blood pressure in strokeprone spontaneously hypertensive rats (59). EC targeting has also been demonstrated with adeno-associated viral (AAV) vector (60). This was achieved via incorporation of an ECspecific peptide cDNA into the VP3 region of the AAV-2 capsid such that the peptide was expressed at the virion 25,000 branched polyethyleneimine (MW=25,000, Sigma-Aldrich); C2 cross-linker with a hydroxyethyl side chain group, EDA ethylendiamine, DMEDA N,N' dimethylethylenediamine, TMEDA N,N,N'N'-tetramethylethylenediamine.…”
Section: Targeted Delivery Of Viral Vectors To Pulmonary Endotheliummentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted delivery of endothelial nitric oxide synthase (eNOS) transgene to ECs prevented elevation of blood pressure in strokeprone spontaneously hypertensive rats (59). EC targeting has also been demonstrated with adeno-associated viral (AAV) vector (60). This was achieved via incorporation of an ECspecific peptide cDNA into the VP3 region of the AAV-2 capsid such that the peptide was expressed at the virion 25,000 branched polyethyleneimine (MW=25,000, Sigma-Aldrich); C2 cross-linker with a hydroxyethyl side chain group, EDA ethylendiamine, DMEDA N,N' dimethylethylenediamine, TMEDA N,N,N'N'-tetramethylethylenediamine.…”
Section: Targeted Delivery Of Viral Vectors To Pulmonary Endotheliummentioning
confidence: 99%
“…surface (60). We have shown that redirecting of an Ad vector to pulmonary endothelium can also be achieved via a simple sequential injection of cationic liposomes followed by the viral vector (61).…”
Section: Targeted Delivery Of Viral Vectors To Pulmonary Endotheliummentioning
confidence: 99%
“…However, it has also been demonstrated that the same peptide can behave differently when inserted into different regions on the AAV capsid surface, presumably due to local conformational differences (Grifman et al, 2001;Shi et al, 2001;Wu et al, 2000). Accordingly, peptides selected for the ability to mediate phage binding to a given cell type can suffer losses in targeting capacity when incorporated into AAV (Work et al, 2006). It is therefore arguable that it would be preferable to select for novel peptide specificity in the context in which it will be ultimately utilized, that is, directly within the AAV capsid.…”
Section: Transductional Targeting Of Aavmentioning
confidence: 99%
“…4 Adeno-associated virus 2 (AAV2) has been investigated for many gene therapy applications and it has been shown to have many desirable properties, such as an ability to produce relatively long-term transgene expression in vivo. However, systemic administration of AAV2 results in a very low level of transduction of vascular cells 5,6 and the majority of the virus is found in the liver and spleen. 7,8 The primary receptor for AAV2 is heparan sulphate proteoglycan (HSPG).…”
Section: Introductionmentioning
confidence: 99%
“…9 Insertion of targeting peptides into the HSPG binding site (after residue 587) ( Figure 1a) has been shown to reduce the natural tropism of the virus and retarget it to alternative cell types in vitro and in vivo. 5,6,[10][11][12] Therefore a single modification can both detarget and retarget the vector, although the efficiency of this is peptide dependent.…”
Section: Introductionmentioning
confidence: 99%